Waste less time on Facebook — follow Brilliant.
×

Complex roots part 3 - Product of the roots

\[\prod_{x = 0}^{n - 1}{Z_x} =~ ?\]

The last note proved that the sum of all the roots is equal to zero. This note is going to explore what answer the product of all the roots gives.

Let's start.

\[Z_x = \sqrt[n]{z} = \sqrt[2n]{a^2 + b^2} \cdot \text{cis}\left(\frac{\arctan \frac{b}{a}}{n} + \frac{2x\pi}{n}\right)\]

\[\prod_{x = 0}^{n - 1}{Z_x} = Z_0Z_1Z_2\cdots Z_{n - 1}\]

There are \(n\) terms.

\[\prod_{x = 0}^{n - 1}{Z_x} = \sqrt[2n]{a^2 + b^2}^n \cdot \text{cis}\left(\frac{\arctan\frac{b}{a}}{n}\right)\text{cis}\left(\frac{\arctan\frac{b}{a}}{n} + \frac{2\pi}{n}\right)\text{cis}\left(\frac{\arctan\frac{b}{a}}{n} + \frac{4\pi}{n}\right)\cdots \text{cis}\left(\frac{\arctan\frac{b}{a}}{n} + \frac{2(n - 1)\pi}{n}\right)\]

\[\prod_{x = 0}^{n - 1}{Z_x} = \sqrt{a^2 + b^2} \cdot \text{cis}\left(n\frac{\arctan\frac{b}{a}}{n} + \frac{2\pi + 4\pi + \cdots + 2(n - 1)\pi}{n}\right)\]


\[2\pi + 4\pi + \cdots + 2(n - 1)\pi = 0 + 2\pi + 4\pi + \cdots + 2(n - 1)\pi\]

There is now \(n\) terms rather than \(n - 1\) terms.

\[\sum_{x = 0}^{n - 1}{2x\pi} = \frac{n(2\pi)(n - 1)}{2}\]

\[\sum_{x = 0}^{n - 1}{2x\pi} = n\pi(n - 1)\]

\[\sum_{x = 0}^{n - 1}{2x\pi} = n^2\pi - n\pi\]


\[\prod_{x = 0}^{n - 1}{Z_x} = \sqrt{a^2 + b^2} \cdot \text{cis}\left(\arctan\frac{b}{a} + \frac{n^2\pi - n\pi}{n}\right)\]

\[\prod_{x = 0}^{n - 1}{Z_x} = \sqrt{a^2 + b^2} \cdot \text{cis}\left(\arctan\frac{b}{a} + n\pi - \pi\right)\]

\[\prod_{x = 0}^{n - 1}{Z_x} = \sqrt{a^2 + b^2} \cdot \text{cis}\left(\arctan\frac{b}{a}\right)\text{cis}(n\pi - \pi)\]


\[\sqrt{a^2 + b^2} \cdot \text{cis}\left(\arctan \frac{b}{a}\right) = re^{\theta i} = z\]


\[\prod_{x = 0}^{n - 1}{Z_x} = z\text{cis}(n\pi - \pi)\]

\[\prod_{x = 0}^{n - 1}{Z_x} = z\frac{\text{cis}(n\pi)}{\text{cis}(\pi)}\]


\[\text{cis}(\pi) = \cos(\pi) + i\sin(\pi) = -1 + 0i = -1\]


\[\prod_{x = 0}^{n - 1}{Z_x} = z\frac{\text{cis}(n\pi)}{-1}\]

\[\prod_{x = 0}^{n - 1}{Z_x} = -z\text{cis}(n\pi)\]

\[\prod_{x = 0}^{n - 1}{Z_x} = -z\text{cis}(\pi)^n\]

\[\prod_{x = 0}^{n - 1}{Z_x} = -z(-1)^n\]

\[\prod_{x = 0}^{n - 1}{Z_x} = -(-1)^nz\]

\[\prod_{x = 0}^{n - 1}{Z_x} = (-1)^{n + 1}z\]

In conclusion, if \(n\) is even then the product of the roots is \(-z\), if \(n\) is odd then the product of the roots is \(z\).


\[\text{When }n\text{ is an even number}:~\prod_{x = 0}^{n - 1}{Z_x} = -z\]

\[\text{When }n\text{ is an odd number}:~\prod_{x = 0}^{n - 1}{Z_x} = z\]


Hope you enjoyed the note

Note by Jack Rawlin
6 months, 3 weeks ago

No vote yet
1 vote

Comments

Sort by:

Top Newest

Awesome article..Worth reading. Amar Mavi · 6 months, 3 weeks ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...